Human immunodeficiency virus reverse transcriptase: steady-state and pre-steady-state kinetics of nucleotide incorporation - Reardon, J E (Biochemistry (Easton), 1992)
Steady-state and pre-steady-state kinetic constants were determined for reverse transcriptase catalyzed incorporation of nucleotides and nucleotide analogues into defined-sequence DNA primed-RNA templates. 3'-Azido-3'-deoxythymidine 5'-triphosphate (AZTTP) was almost as efficient a substrate (kcat/Km) as dTTP for the enzyme. In contrast, the four 2',3'-dideoxynucleoside 5'-triphosphates and 3'-deoxy-2',3'-didehydrothymidine 5'-triphosphate (d4TTP) were 6-30-fold less efficient substrates of the enzyme. The kcat values for all nucleotide analogues were similar, consistent with a kinetic model in which the steady-state rate-limiting step was dissociation of the template-primer from the enzyme [Reardon, J. E., & Miller, W. H. (1990) J. Biol. Chem. 265, 20302-20307]. The pre-steady-state kinetics of single-nucleotide incorporation were consistent with the kinetic model: [formula: see text] where E, TP, and dNTP represent reverse transcriptase, a defined-sequence DNA primed-RNA template, and 2'-deoxynucleoside 5'-triphosphate (or analogue), respectively. The dissociation constant (Kd1) for template-primer binding was 10 nM, and the estimated rate constants for association and dissociation of the enzyme.template-primer complex were 4 x 10(6) M-1 s-1 and 0.04 s-1, respectively. The dissociation constants (Kd2) for dTTP, AZTTP, and 3'-deoxythymidine 5'-triphosphate (ddTTP) were 9, 11, and 4.6 microM, respectively. Thus, the differences in steady-state Km values were not due to differences in binding of the nucleotide analogues to the enzyme. In contrast, the rate-limiting step during single-nucleotide incorporation (kp) was sensitive to the structure of the nucleotide substrate.